TECHNOLOGY AND SCIENCE-BASED EDUCATION AS A PILLAR OF INTELLECTUAL DEVELOPMENT IN THE 21ST CENTURY: A LITERATURE REVIEW ON THE DEVELOPMENT OF ADAPTIVE, INCLUSIVE, AND SUSTAINABLE LEARNING MODELS IN THE DIGITAL AGE - Ismaul Fitroh; Aslan Aslan (Adisam Publisher, 2026)
This study aims to examine the role of technology and science-based education as a pillar of intellectual development in the 21st century through a literature review approach. Digital transformation has changed the paradigm of education from a conventional model to an adaptive, inclusive, and sustainable learning system. Technology not only functions as a learning tool, but also as a catalyst for the formation of a creative, critical, and innovative knowledge-based society. This study highlights how the integration of technology and science strengthens intellectual competitiveness through expanded access, personalised learning, and the strengthening of 21st-century competencies such as critical thinking, collaboration, communication, and digital literacy. In addition, a conceptual framework for adaptive, inclusive, and sustainable learning models has been developed as a strategic solution to global challenges in modern education. The results of the study show that the successful implementation of this model depends on the readiness of human resources, digital infrastructure support, and progressive and humanistic education policies. Thus, technology- and science-based education not only improves academic quality but also shapes intellectual and social characters that are relevant to the demands of the digital age without abandoning human values